2009
DOI: 10.1007/s10488-008-0202-y
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare Recommendations to Improve Mental Health Services for Children who have Experienced Abuse and Neglect: A National Perspective

Abstract: This study uses a key informant approach to understand the nature, extent, and quality of outpatient mental health services for children in the child welfare system (CWS) in the United States. We interviewed 89 county child welfare administrators to determine the status of outpatient mental health services and provide recommendations for enhancing care and service delivery. Developed for this study (Caring for Children in Child Welfare), the interview was incorporated in the second formal data collection wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Further, similar to previous findings (Kolko et al, 2009; Phillips & Zhao, 2010), children in our study exposed to the arrest of a family member were more likely to also have been exposed to other types of PTEs compared to those not exposed to arrest. Per caregiver report, almost all of the children who had been exposed to an arrest had also been exposed to multiple types of PTEs beyond the arrest of a family member, including domestic violence, separation from a loved one, or death of someone close.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further, similar to previous findings (Kolko et al, 2009; Phillips & Zhao, 2010), children in our study exposed to the arrest of a family member were more likely to also have been exposed to other types of PTEs compared to those not exposed to arrest. Per caregiver report, almost all of the children who had been exposed to an arrest had also been exposed to multiple types of PTEs beyond the arrest of a family member, including domestic violence, separation from a loved one, or death of someone close.…”
Section: Discussionsupporting
confidence: 91%
“…Per caregiver report, almost all of the children who had been exposed to an arrest had also been exposed to multiple types of PTEs beyond the arrest of a family member, including domestic violence, separation from a loved one, or death of someone close. This mirrors research stating that children who experience the arrest of a family member are more likely to experience other types of PTEs (Kolko et al, 2009; Philips & Zhao, 2010, Snyder et al, 2012). …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There is some evidence that interventions that are the most effective for children and adolescent affective disorders, are also the most cost-effective (Domino et al 2008;Haby et al 2004). Presently, as a recent survey of county child welfare administrators suggests, there is a high degree of variability in the implementation of evidence-based services (Kolko et al 2009). The second directions relates to characteristics such as age, ethnicity, and gender that are not directly amenable to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that children who have been exposed to arrest of a family member are significantly more likely to have been the victims of, or witness to, a broader range of violent and nonviolent crimes in their homes including child maltreatment or the use/selling of illegal substances [24]. Children exposed to the arrest of their parent have a greater likelihood of developing serious emotional and behavioral problems than children without this history [5], including children from the general population [6] and children from highrisk populations such as those involved in the child welfare system [7].…”
mentioning
confidence: 99%